INVESTIGATION OF THE PROCESS OF DYING WITH DISPERSIVE DYES OF FABRIC FROM POLYESTER-BAMBOO FIBERS (World Economics and Finance Bulletin, 2022)
This article discusses the possibilities of chemical finishing of mixed polyesterbamboo fabric with dispersed dyes. The purpose of this study is to obtain a mixed fabric based on bamboo and polyester fiber and to develop a technology for dyeing with disperse dyes. The object of the study was a blended fabric made of polyester and bamboo fibers with technical characteristics, 140 cm wide, 36 g/m2 surface density, the number of threads per 10 cm of fabric, 352 warp, 350 weft
Keywords: Polyester fiber; bamboo fiber; dyeing; disperse dyes